Back Cover: Mechanically Induced Multicolor Change of Luminescent Materials (ChemPhysChem 9/2015). Issue 9 (22nd June 2015) - Ma, Zhiyong; Wang, Zhijian; Teng, Mingjun; Xu, Zejun; Jia, Xinru
<x xml:space="preserve">Abstract</x> On p. 1811, X. Jia et al. review fluorescent materials that undergo mechanically induced multicolor changes. Topics are categorized according to the different applied forces that are required to induce the multicolor change, including mechanical control of either the supramolecular structures or the chemical structures, and mechanical control of both the supramolecular structures and chemical structures.